Mobile Computing: Theory and Practice
This book provides an insight into all the key technologies available to facilitate mobile computing, including wireless and wireless and cellular communication, WLANs, logical mobility, handheld devices and their operating systems, physical mobility, mobile ad hoc networks, and the mobile internet. Apart from the theory, many example projects and suggestions for hands-on programming have been provided to facilitate better understanding of the underlying concepts.